Sistem Pendukung Keputusan Untuk Menentukan Tempat Gymnastic Terbaik di Kota Medan Mengunakan Metode TOPSIS - Amin Rahman (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Decision support system as a computer-based system consisting of components between system components (language). Knowledge system components and problem processing system components that interact with one another. Decision support system is a approach or methodology to support decisions, CBIS (computer based information system) that is flexible, interactive and adaptable, which was developed to support solutions for specific management problems that are not structured. To help the problems faced by the decision support system in determining / placement of the best Gym, where the selection is seen from the symptoms and strengths of each place. Using the Topsis method (Technique for Order Preference by similarity to Ideal Solution) is expected in the decision support system to calculate the results from the best value of the Gym